Simula Research Laboratory by Thinking Constantly about it - Tveito, Aslak; Bruaset, Are Magnus; Lysne, Olav (Springer Berlin Heidelberg : Imprint: Springer, 2010)
The Simula Research Laboratory, located just outside Oslo in Norway, is rightly famed as a highly successful research facility, despite being, at only eight years old, a very young institution. This fascinating book tells the history of Simula, detailing the culture and values that have been the guiding principles of the laboratory throughout its existence. Dedicated to tackling scientific challenges of genuine social importance, the laboratory undertakes important research with long-term implications in networks, computing and software engineering, which includes offering a Centre of Excellence in biomedical computing. The text covers every angle: the laboratory's background and political context, the work it has completed, its approach to the education and development of its researchers, and the organisation's efforts to promote the application of its research results. The key research projects and results are covered in separate chapters, each of which is preceded by a thumbnail description of the project and how the research is useful for society. As well as explanatory text, the other chapters feature interviews with major players in the facility's history, both inside Simula, among its collaborators, and in Norwegian society at large.